2011
DOI: 10.4269/ajtmh.2011.10-0207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Urine on Cell Cycle and Infectivity of Leismania Species Promastigotes In Vitro

Abstract: Abstract. In vitro cultivation of Leishmania parasites plays an important role in diagnosis and treatment of leishmaniasis and in vaccine and drug development studies. Conversely, long-term cultivation of Leishmania parasites usually results in decreased infectivity potential. Some studies reported a stimulatory effect of human urine in Leishmania promastigotes. However, there is no information about the effects of urine within culture on the infectivity of Leishmania parasites. Analysis of the effect of urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Human urine is a clear example of a media component with a specific biological imprint. When used as a medium supplement it increases parasite proliferation (Shamsuzzaman et al 1999) and infectivity (Allahverdiyev et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Human urine is a clear example of a media component with a specific biological imprint. When used as a medium supplement it increases parasite proliferation (Shamsuzzaman et al 1999) and infectivity (Allahverdiyev et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamins act as co-factors enabling many enzymes to function properly in cells, and in some cases are essential where cells cannot synthesize them, so a vitamin supplement is often required in media. Several reports have shown that 1-5% (v/v) human urine can stimulate the growth of Leishmania promastigotes ( Howard et al., 1991 ; Singh et al., 2000 ; Iqbal et al., 2006 ; Allahverdiyev et al., 2011 ). Allahverdiyev et al.…”
Section: Discussionmentioning
confidence: 99%
“…This study mentioned that higher concentrations of urine were not as good, probably because of a fall in pH and inhibitory concentrations of human metabolites [13]. But a research reported that human urine in parasite cultures differentially affected and increased the infectivity and proliferation of Leishmania species promastigotes and facilitated the transition from G0/G1 to S phases more quickly and their results have shown that promastigotes could efficiently proliferate and grow in culture media containing relatively high (25%) urine concentrations [40]. In our previous researches about finding suitable replacements for FCS we had found that the serum and the urine of many animals like hamster, rabbit, and sheep are suitable for cultivation of promastigotes, but, collecting the serum of some of them, like Hamster, is expensive and using of some of them, like sheep serum, is accompanied with many challenges about adaptation problems of promastigotes to new serum (unpublished work).…”
Section: Discussionmentioning
confidence: 99%